2018
DOI: 10.14254/2071-789x.2018/11-4/8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of financial development and trade openness on Nigeria‘s dynamic growth

Abstract: This study attempts to investigate the short and long-run cointegration with the causal nexus between financial developments, trade and output growth in Nigeria. The financial instability index was generated using the residual based analysis to account for the effect of financial instability on growth. To examine the cointegration effects, the study used Autoregressive Distributed Lag (ARDL) model. The non-Granger causality analysis was also employed to determine the direction of causality between the variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The same situation was observed in the studies conducted on economic growth in relationship with financial instability. Few studies examined the relationship between financial instability and economic growth (Danlami et al, 2018. Jayakumar et al, 2018, Bouheni and Hasnaoui, 2017, Creel et al, 2015Klomp and Haan, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The same situation was observed in the studies conducted on economic growth in relationship with financial instability. Few studies examined the relationship between financial instability and economic growth (Danlami et al, 2018. Jayakumar et al, 2018, Bouheni and Hasnaoui, 2017, Creel et al, 2015Klomp and Haan, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These studies found a mixed relationship between economic growth and financial instability. Few studies suggest a negative relationship between economic growth and financial instability (Guerineau and Leon, 2019; Danlami et al, 2018;Batuo et al, 2018). This indicates that the increase in the economy's growth promotes stability of the financial sector and a decline in instability.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this study. While the impact of trade and financial liberalisation on growth and macroeconomic variables has been extensively researched in Nigeria (Akpan, 2004;Kaita, 2015;Saifullahi and Tanimu, 2015;Danlami et al, 2018;Aigheiyisi and Isikhuemen, 2018;Apanisile and Okunlola, 2020;Aremo and Arambada, 2021;among others), little attention has been paid to unravel the impact of trade and financial liberalisation on current account balance. Several studies looked at macroeconomic and institutional factors, monetary policy, fiscal policy shock, and adjustment policy as determinants of current account (Longe, Muhammad, Ajayi and Omitogun, 2019;Danmola and Olateju, 2013;Uneze and Ekor, 2012;Oshota, 2015;Udah, 2010;Chete, 2001;Kudaisi and Olomola, 2019;Sule and Shuaibu, 2020;among others).…”
Section: Introductionmentioning
confidence: 99%
“…M. Danlami, N. Loganathan, D. Streimikiene, A. Mardani, A. Golam Hassan [15] argue that the goal of each country is to achieve sustainable economic growth that will lead to economic development in the long run, and many sectors of the economy will contribute to the growth of the nation. However, it is difficult to find out whether financial development leads to economic growth in the long run or vice versa.…”
mentioning
confidence: 99%